RAPE AND SHAME IN J.M. COETZEE’S DISGRACE (LITERA KULTURA : Journal of Literary and Cultural Studies, 2014)
RAPE AND SHAME IN J.M. COETZEE’S DISGRACE Salman Muhiddin English Literature, Faculty of Languages and Arts, Surabaya State University salmanlatieff@gmail.com Drs. Much. Khoiri, M.Si English Department, Faculty of Languages and Arts, Surabaya State University much_choiri@yahoo.com Abstrak Pemerkosaan adalah setiap tindakan yang tidak diinginkan , manipulasi atau pemaksaan dalam bentuk aktivitas seksual. Tindakan pemerkosaan berdampak bagi pemerkosa dan korbannya. Dampaknya terhubung ke masalah psikologis , seperti kecemasan , depresi , dan gangguan mental lainnya serta perilaku moral yang bermasalah. Skripsi ini difokuskan pada tindak perkosaan yang dialami oleh karakter dan bagaimana hal itu menyebabkan rasa malu dalam novel Disgrace karya JM Coetzee. Secara khusus, tujuan skripsi ini adalah untuk mendeskripsikan bagaimana gambaran perkosaan yang dialami oleh karakter dan untuk mengungkapkan bagaimana perkosaan itu menyebabkan rasa malu dalam novel Disgrace karya J.M. Coetzee. Dalam analisisnya, skripsi ini menggunakan beberapa proses analisis , yaitu: (1) mengklasifikasikan kutipan-kutipan yang sejalan dengan masalah laporan, (2) menggambarkan tindakan perkosaan yang telah dialami oleh karakter, (3) mengungkapkan bagaimana pemerkosaan menyebabkan malu. Hasil analisis menunjukkan bahwa ada tiga macam pemerkosaan yang digambarkan dalam cerita. Pemerkosaan pertama terjadi antara David dan pekerja seks bernama Soraya. Pemerkosaan kedua terjadi antara David dan muridnya, Melanie. Yang ketiga dialami oleh putri David, Lucy. Setelah pemerkosaan itu, pelaku dan korban perkosaan merasa malu. David sebagai pemerkosa mendapatkan aib dan tekanan publik dari komite universitas dan mahasiswanya. Dia kemudian meminta maaf kepada keluarga Melanie. Sedangkan korban akan merasa malu untuk tampil di publik karena mereka takut aibnya terbongkar. Kata Kunci: Pemerkosaan, Malu, Aib Abstract Rape is any unwanted, manipulated or coerced forms of sexual activity. The act of rape has an impact to both the rapists and the rape survivors. The impact is connected to psychological problems, such as anxiety, depression, and other mental disorders as well as problematic moral behaviour. This study focuses on the characters’ experience in raping and being raped, and how it leads to shame in J.M. Coetzee’s Disgrace. In particular, the purpose of this study is to describe how rape is depicted by the characters and to reveal how the characters’ rape leads to shame in J.M. Coetzee’s Disgrace. In the analysis, this study does some processes of analysis, they are: (1) classifying the quotations which are in line with the problem of statements, (2) describing the rape that has been experienced by the characters, (3) revealing how rape leads to shame. The result of the analysis shows that there are three kinds of rape which is depicted in the story. The first rape is happened between David and the prostitute named Soraya. The second rape is between David and his student, Melanie. The third one is experienced by David’s daughter, Lucy. After the rape, the rapist and the rape survivors get shame. David is getting disgrace and gets public pressure from the university committees and the students. He then ask for apologize to Melanie’s family. While the rape survivors are getting shame after being raped. They are shame to make a public appearance because they are afraid of being discovered or found out by another person. Keywords: Rape, Shame, Disgrace INTRODUCTION The definition of rape varies state-to-state and can include anything from touching to actual penetration, but, generally, rape is any “unwanted, non-consensual, manipulated or coerced forms of sexual activity” (http://www.umich.edu). The act may be carried out by physical force, coercion, abuse of authority or against a person who is incapable of valid consent, such as one who is unconscious, incapacitated, or below the legal age of consent. The term rape is sometimes used interchangeably with the term sexual assault, and the term of violent change into rape survivor. The rape effects can include both physical trauma and psychological trauma. Rape will also lead to shame. The feeling is connected to psychological problems such as eating disorders, substance abuse, anxiety, depression, and other mental disorders as well as problematic moral behavior. The shame is also reformed from some culture that sees the rape victims are dirt. For example, a rape victim especially one who was previously a virgin, may be viewed by society as being damaged. According to Alliance, victims in these cultures may suffer isolation, be disowned by friends and family, be prohibited from marrying, and be divorced if already married, or even killed. This phenomenon is known as secondary victimization. Secondary victimization is the re-traumatization of the sexual assault, abuse, or rape victim through the responses of individuals and institutions. Rape also affects the rapist. If someone known as a rapist he will be the public enemy. The rapist may lose their dignity, job, and friends. Punishment for rape in most countries today is imprisonment. Thus he will get ashamed but the right term for rapist is disgrace. On the previous study Feminine Shame Masculine Disgrace, Nurka put little bit different from shame, “people with disgrace will automatically being shame. Disgrace is brought from without (‘put to shame’), or is directed outward from its source (‘a person who or thing which is the cause or source of disgrace’).” (Nurka, 2012: 311). J.M. Coetzee is a South African writer born under the apartheid government. Coetzee is unveiling many fragile topics in South Africa from many of his books. He elegantly put the theme rape over the race to depict the social condition of ‘New South Africa’. Rape of women by men has occurred throughout recorded history and across cultures. As the novel background, South Africa is often labeled the rape capital of the world. The prevalence of rape, and particularly multiple perpetrator rape, is unusually high. Coetzee puts the concept of rape and shame in novel ‘Disgrace’. The narrative follows a white South African professor’s, David Lurie, escape to his daughter’s farm, after he raped his student, Melanie. The farm is soon attacked and robbed by three black men, and the daughter raped. As father and daughter piece together their strained relationship and individual lives, they must reconcile their positions in the “New South Africa,” to Lucy, is gang-raped by three men on her smallholding in the Eastern Cape, but she chose to say nothing about what happened to her. She decided to take the shame on her own. While on David, he rents a room in Grahmstown to help his daughter at the market once a week and to dedicate himself to the disposal of the dogs' bodies at the shelter. He cannot back to Cape Town because he has nothing left there for his disgrace. The university had replaced him with another professor. Once he went to Melanie house bring up all his disgrace to ask for forgiving to her parents for what he did through Melanie and family. In accordance of background study above, it can be simplify to discuss among two problems that emerge as significant concern toward this novel. How rape is depicted by the characters in J.M. Coetzee’s Disgrace? How the characters’ rape leads to shame in J.M. Coetzee’s Disgrace? To answer the first problem, this study uses the concept of rape. Rape is a multidetermined behaviour that will ultimately be explained only by models incorporating a multitude of dimensions.” (Prenkty and Knight, 1991: 657). The dimensions that are possibly to explain rape are through feminist theory, evolutionary theory, self-controlled theory, narcissistic theory, and crime theory. (Lowell, 2010: 159-161). Those theories can be used to help explain how rape occurs. Feminist theorists explain that the culture of male dominance is responsible for rape occurring. On his book Rethinking Rape, Cahill simply delivered that feminist theorists assert that rape is only one symptom of the larger problem of a male dominated society. Feminist theorists see rape as more of a violent act than a sexual act, and claim that rape is inspired by political motivations to dominate and degrade. Feminist theorists also deny that rape has an individualistic nature, but claim that rape is “nothing more or less than a conscious process of intimidation by which all men keep all women in a state of fear” (Cahill, 2001:16). Self control theory can lead to a man committing rape against a female. It is based on the premise that the male sex drive is uncontrollable. Men with this belief say that their sexual urges cannot be controlled and they are not responsible for their actions. Proponents of this theory “[propose] both that men’s sexual energy is difficult to control and that women have a key role in its loss of control,” since women deny sex to men who have to relieve their sexual drive (Polaschek & Ward, 2002, p. 13). This theory can be tied to Gottfredson and Hirschi’s low self-control theory. Low self-control theorists posit that, since criminal acts provide immediate gratification, criminals will engage in them because they are not able to defer gratification. A biological explanation of rape includes Thornhill and Palmer’s evolutionary theory of rape .Proponents of this theory claim that those men who were able to force their sexual desires on women were able to reproduce more efficiently, and thus have more offspring with their traits. Thornhill and Palmer are “dismissive of rape theories that emphasize the role of culture and learning in the acquisition of rape-prone traits, arguing that culture is only possible because individuals have evolved capacities that enable them to learn” (Siegert & Ward, 2002:6). Another theory that can explain rape is the narcissistic reactance theory, which is also tied to Gottfredson and Hirschi’s (1990) low self-control theory. In this theory, narcissists are defined as having a “lower proneness to shame and guilt,” having “unrealistically positive self-evaluations,” and being “especially likely to respond to bad evaluations by blaming other sources, including the evaluator and the technique of evaluation” (Baumeister et al., 2002: 3). These theorists claim that the, “tendency to respond to esteem threats by getting angry and blaming others may contribute to the elevated level of interpersonal difficulties that narcissists report” (Baumeister et al., 2002: 4). The second problem is using the concept of shame. Some victims of rape are feeling dirty, devalued, and humiliated as a result of a sexual assault. Feelings of shame are often related to the powerlessness and helplessness victims experience during a sexual assault. Shame may also be a reaction to being forced by the assailant to participate in the crime. Shame is the painful feeling of having done or experienced something dishonourable, improper and foolish. Shame is what prevents many survivors from speaking about what happened to them. Shame is an attack on the survivor as a person. It is the feeling you get when you are sure that someone will think poorly of you because you were assaulted. Shame is longer lasting, and ultimately more dangerous than guilt. The feeling of shame is so intense for rape victims that many of them never tell anyone what happened to them. Even in psychotherapeutic settings, victims of rape often avoid talking about what happened to them. (http://www.healthyplace.com/abuse/articles/guilt-and-shame-of-being-raped/, retrieve on: 15 April 2014). Shame is already bears the germ of guilt. Shame becomes guilt when the social norms are internalized as one’s own feelings of value and when self-condemnation anticipates public exposure. This presupposes the development of a personal centre, with the beginning capacity to regard oneself as the originator of one’s actions, to evaluate and feel responsible for them. In contrast to shame, guilt is no more bound to the immediate presence of the other; its impact is more lasting. The event one is to be blamed for sin in the past. Thus the present rejection of shame becomes the already executed expulsion of elementary guilt. Instead of being exposed to, and paralyzed by, the others’ gazes, the culprit feels, as it were, already abandoned. (Thomas Fuchs, 2003: 8). RESEARCH METHOD Research method that used in this analysis here must be qualified as an applying in literary appreciation. The thesis is regarded as a descriptive-qualitative study and uses a library research. This study uses novel of J.M. Coetzee, entitled Disgrace that published by Vintage, Random House, 20 Vauxhall Bridge Road, London, Great Britain, 1999 as the main data of the study. The data are in the form of direct and indirect speech of the characters, dialogues, epilogues and quotations which indicate and represent aspect of rape by the characters that lead to shame. This thesis is using the library method in collecting the data. It does not use the statistic method. That is why it is not served in numbering or tables. Library research used an approach in analyzing this study. The kind of library research which is used here is intensive or closely reading to search quotations or phrases. It also used to analyze the literary elements both intrinsic and extrinsic. The references are taken from library and contributing ideas about this study from internet that support the idea of analyzing. The analysis is done by the following steps: (1) Classification based on the statement of the problems. This classification is used to avoid the broad discussion. There are two classifications in this study. They are the depiction of rape and how it leads to shame. (2) Describing David Lurie’s and Lucy’s rape which is stated from the quotations or statements. (3) Describing how the shame and disgrace they got which is stated from the quotations or statements. (4) Revealing the relations between rape and shame. The quotations that showed how the characters’ rape leads to shame are taken as data. (5) Drawing the conclusion based on the analysis which is in line with the problems. ANALYSIS The first analysis is the depiction of rape. In Disgrace the rape parted in three different background and motif. The first rape is from David to Soraya the prostitute woman. David uses his financial advantages to buy woman for sex. After the relationship with Soraya ended David engage to a scandal with his Student Melanie. David admits that he misused his authority as a lecturer to have sex with his student. This depicts the condition of male domination particularly in South Africa. The last rape happened to David’s’ daughter, Lucy. She raped by three black African intruders. The rape of Lucy remains mystery for her silence to not tell the policemen about the incident. In his age of fifty two, and divorced, David proclaim that he has solved problem of sex rather well even without a wife. However, the reason of his ‘solved problem of sex’ for over one year is Soraya, a high-class prostitute girl from an escort service. She is a coloured woman that David has a historical interest. She has a honey brown body. She is tall and slim, with long black hair and dark, liquid eyes. Simply said this beautiful girl becomes his sources of happiness. “It surprises him that ninety minutes a week of a woman's company are enough to make him happy, who used to think he needed a wife, a home, a marriage” (Coetzee, 1999:5). David’s ideal marriage is with a wife that is a prostitute, but for him only and only at certain times. He met Soraya only on Thursday. On the other day he is back to his normal life. With Soraya he already find the happiness he belief. It makes him thought; there is no need to search for another life destination such as home and real wife. It made David rely on prostitution in his sexual life. Prostitution as the solution allows him to fantasize that a woman mirrors his wishes. He bought sex he wanted and she got extra money from him. For David money is no problem concerning that he lived alone with his salary as a professor and lecturer. As a consequence, he paid double for her. At least his money is worthy for finds her entirely satisfactory. As a customer, David is on dilemma seeing this prostitution. He knows that every woman in the prostitution is perforce. Women in prostitution would leave if they could. The term is an indicator of their hopelessness. “They tell stories, they laugh, but they shudder too, as one shudders at a cockroach in a washbasin in the middle of the night” (Coetzee, 1999:8). In their mind, they see that women in prostitutes are disgusted with their customer, so does the customers. Soraya just pretended to keep their customer satisfied. Prostitutes sometimes talk of the feeling of power they experience when they are with their customer. They are talking about a feeling of control when engaged in sexual acts. They soon feel the disadvantages of that particular way of life. It also exposes the fragility of the illusion of control over what another subject wants. If a man wants a woman to want what he wants, he can only force her to pretend to want his desire and then he has also to deny that pretence. David then met Melanie, his student. He treats her under the wine and romantic music, the Mozart clarinet quintet. He made his move to seduce Melanie in some conversation. He talked about poetry, music, food, and his past life. Then, after he offered some liqueur, the higher alcoholic drink, he said directly to Melanie, asking her to do something reckless. He touch her and said “You're very lovely ... Stay. Spend the night with me.” (Coetzee, 1999: 16). Melanie refused his liquor but accept a shot of whisky in her coffee. She should say no at that time instead wonder and ask why. She trapped to this conversation: ‘Why?’ ‘Because you ought to.’ ‘Why ought I to?’ ‘Why? Because a woman's beauty does not belong to her alone. It is part of the bounty she brings into the world. She has a duty to share it.’ (Coetzee, 1999: 16) As a professor of language and communication, David, could easily manipulate the words, he says. The way he talked to Melanie reflects his experience through many women. “Smooth words, as old as seduction itself.” (Coetzee, 1999: 16). He says it indirectly to make Melanie believes what he belief. He makes the statement so convincing and become hard to decline. Melanie herself was mistaken to ask more to David, because she did not know how to deal with him. Instead saying ‘why’, she should say ‘no’ to David when he asked her to stay. So she would not get in this complicated situation. Maybe she should already say ‘no’ when David asked her to come to his house. David was in a grip of something and he would not let it go. However, what is done is done. The next day David asked Melanie to go lunch. Again, Melanie cannot reject David offer. There is still time for her to tell a lie but she is too confused, and the moment passes. In the restaurant, they got an awkward situation because Melanie lost her appetite and there was a long silent. Then David asked to Melanie about what is on her mind: `Is something the matter? Do you want to tell me?' She shakes her head. `Are you worried about the two of us?' `Maybe,' she says. `No need. I'll take care. I won't let it go too far.' Too far. What is far, what is too far, in a matter like this? Is her too far the same as his too far? (Coetzee, 1999: 19) After the harassment from David a day before, Melanie must wonder about his plan. The women should worry about her safety. Because feminist, Cahill, agree that one of the rape purpose is to take women into state of fear, and it is he responsibility of masculinity and the construction of patriarchy. Men are possible to keep women as a fragile creature and need protection. Knowing that Melanie may feel bad about this situation, David guarantees that the thing would not go too far, he put Melanie to feel safe at least. This is another tactical seduction that is done by David. He manipulates the situation and manages it like there is nothing happen like everything is fine. It is not hard for him to do it concerning that Melanie was an easy target for him. The rapist always seeks the powerless people to be his target. Finally, they have sex for the first time. Even though, it is not the first time for both of them. David took Melanie to his house after getting lunch in the restaurant. They did it on the living room with rain sound pattering. Melanie is passive on the first time they have sex. While David finds the act of her passivity is so enjoyable. Melanie is passive like Soraya. She does not crawling, bite, and aggressive. She is his typical woman he was searching for. He was having sex with another whore after Soraya left him. But he did not like it because she is aggressive. So he never does it again with her. His desire was only on Melanie this time. It is stated in the novel that “She struck up a fire in me” (Coetzee, 1999: 166). Fire is a symbolization of energy that can stimulate one’s desire. This fire heat up his libido that pushes him doing something undesired to the core. In the rape theory, David can be considered as narcissistic because he tend to be willing to do whatever it takes to achieve the goal that they want from a relationship, including rape. In this theory, narcissists are defined as having a lower proneness to shame and guilt, having unrealistically positive self-evaluations, and being especially likely to respond to bad evaluations by blaming other sources, including the evaluator and the technique of evaluation. Narcissistic suits David as a rapist. He has lower sense of shame, as teacher and student he took Melanie to go out lunch just the two of them. Considering that he is the famous person in the city, people will wonder what is he up to. In the restaurant he seduced her and ask her to do something wild. He is implying that she has to have sex with him. But the relationship become a scandal that makes him lost his job. After realizing that there's nothing left for him in Cape Town, David wanted to change the atmosphere. He moved to the east across the country to the rural town of Salem in the Eastern Cape, where his daughter Lucy lives alone on a smallholding, growing vegetables to sell at the Saturday market and running a kennel for dogs. David begins a new life there, helping Lucy at the market, assisting Lucy's neighbour Petrus with odd jobs as “I am the gardener and the dog-man” (Coetzee, 1999: 64), and volunteering at the Animal Welfare Clinic with Bev Shaw. Lucy is leftish which make her the reversal of her father. She even did not want call herself a boss by Petrus. She is not individualist but socialist. She helps people no matter who they are. But this time she made big mistake by risk herself to strangers. Lucy tells David to stay outside while she takes the tall man indoors to use the phone. The second man runs in to the house behind them and locks David out. In a total panic, David let go of the bulldog's strap and commanded the dog to go after the boy. Then he kicks down the kitchen door. David tried to save Lucy but he felt someone whack him over the head. He falls down, barely conscious, and feels himself being dragged across the floor. When he realize, he's locked in the bathroom and wondering what's going on with Lucy. The second man comes in to get the car keys from David and then locks him back in. Meanwhile, he looks out and sees the tall man with a rifle. The tall man starts shooting the dogs one by one, splattering brains and guts all over the place. And if that isn't bad enough, the second man and the boy come back in the bathroom, douse David with alcohol, and set him on fire, luckily just his hair catches burning and he extinguishes himself in the toilet. They leave, stealing David's car. David and Lucy are left to deal with everything that just happened. During this whole nightmare, Petrus is nowhere to be found. After being raped, Lucy decided to not report the rape to the police. The silent of Lucy depict the subjugation or conquest. “No I am not blaming you, that is not the point. But it is something new you are talking about. Slavery. They want you for their slave.” (Coetzee, 1999: 159). Lucy response him and disagree with “Not slavery. Subjection. Subjugation.” (Coetzee, 1999: 159). This makes Lucy as the rape survivor depend on men to get protection. The second analysis is about how rape leads to shame. In Disgrace the rape that experienced by the rapist and the rape survivor transform and effect their life worst then before. From the previous study Nurka classified the effect of rape by gender: (1) Female as the object will get shame, (2) men as the subject will take disgrace. (Nurka, 2012: 310). The male character, David Lurie, got disgrace after doing sexual harassment to his student, Melanie. As the rapist, David will be haunted by his sin and losing his reputation and his job. While Lucy, the rape survivor got shame after being raped. The act of rape means to take away by force which the dignity is to be taken. Loosing dignity makes woman feel shameful. It turns out that the act of rape is not only giving shame feeling to the victims but also to the rapist. Soraya knows about the attachment of shame for being prostitute. Then when she met David in the midtown, she was afraid if the public know who she is. This is because David is the famous person in Cape town. “He has always been a man of the city, at home amid a flux of bodies where Eros stalks and glances flash like arrows” (Coetzee, 1999: 6). Concerning that shame is social affect associated with being discovered or found out by another person, she knew that he is the famous person in the city. It is too risky to stay in public with him. There is a high possibility that her secret will spread. Then to keep her pride for her children Soraya decided to quit the job. She did not want her children knows their real mother is. So she decided to resign from the escort and disappeared from that business. David ought to end but he pays a detective to tracking Soraya instead. When he got the number he makes a call. Soraya surprise and wondering abot how he gets the numbers. She did not talk for a moment. She wondered because the agency has a rule about keeping the former prostitutes identity. After the silent she said “I don't know who you are,' she says. ’You are harassing me in my own house. I demand you will never phone me here again, never.” (Coetzee, 1999: 10). After this moment he did not contact Soraya anymore. For Melanie, after she gets the coercive sexual by David, she becomes a different person in class. She even absent when it was on midterm test. Then she told her boyfriend that her professor have sex with her. The boyfriend then angry to him and vandalize his car, deflated the tires and injected a glue on both door. “After this coup de main Melanie keeps her distance. He is not surprised: if he has been shamed, she is shamed too.” (Coetzee, 1999: 31). The gossip may be starting to spread so she tries to not meet him. But on Monday she reappears in class and beside her, leaning back in his seat, hands in pockets, with an air of cocky ease, is the boy in black, the boyfriend. The student in the class knew about what is going on from the gossip. They are clearly waiting to see what the professor will do about the intruder. Professor let the boyfriend intrude to the class but then he asked Melanie to come to the office and tell her to not let the boyfriend do that again. After that moment Melanie never come to the class anymore. Furthermore, after being ashamed she decided to give up her study in the university. Thus her father asked David to tell Melanie to not give up. At this moment, Melanie’s father , Mr. Isaacs did not know that David is the causes of his daughter wanted to quit the university. As David thought “I am the worm in the apple… how can I help you when I am the very source of your woe?” (Coetzee, 1999: 37). After knowing that David rape his Doughter Mr. Isaacs tell him that what e sad done is not right. He imply that he does not sending her daughter to the nest of viper that poisoned her daughter with the act of rape. He feels ashamed about what was happen. He disappointed that an educated person like Professor David do an embarrassing and stupid thing. After the university fired David, Melanie continued her study. From the university scandal Melanie is regarded as victims and the professor is the one who responsible. Thus the disgrace runs to David. Even though Mr. Isaacs’ family got ashamed too from his rape they not reported this to the policemen. David is lucky this time. It is obvious that the rape survivor will blessed with so much shame. It is also happened on Lucy. The first thing she did is staying at home. She does not want to go outside. The trauma and the fear will grow upon her. In earlier days after the rape he stated that he was nothing, heist e dead person. She did not want to meet people too. She would rather hide her face, and he knows why. Because of the disgrace. Because of the shame….. Like a stain the story is spreading across the district. Not her story to spread but theirs: they are its owners. How they put her in her place, how they showed her what a woman was for. (Coetzee, 1999: 115) It is a related to shame that person who gets shame will hide itself from public. Lucy was avoiding he people talk and question. It takes a time to recover from this trauma. But she could not let it go to long because if she do not going outside she will lose her job and stall in the market. To replace her, David and Petrus doing her job in the market. The damage that is given to Lucy, the rape survivor, may attached forever. She felt everything will never be the same. “One is never oneself again?” (Coetzee, 1999: 124). Is “Lucy” still “Lucy”? Lucy also emphasizes the existence of herself “I am not the person you know. I am a dead person and I do not know yet what will bring me back to life.” (Coetzee, 1999: 161). With nothing to left she got nothing to lose. Then she decided to take consequences of human body in pain. Lucy takes the consequences of human body in pain. “I must learn to accept. To start at ground level. With nothing. Not with nothing but. With nothing. No cards, no weapons, no property, no rights, no dignity.” (Coetzee, 1999: 205). From the sentence above it is shown that Lucy is starting to understand her condition after being raped. She decided to start her business in farm and her vendor. Although she realises that she has nothing left. The rapist also takes her dignity that is the biggest loose after the rape. A woman without a dignity will judge herself as a shameful person. She also feels that she has no right to her own land and properties. It is because Petrus take over it. As the rapist, David Lurie got public pressure from university committee and the students. At first he does not confess that he is guilty. But after her daughter being raped by three African intruders he contemplate and change his attitude. Then he ask for apologize to Melanie’s family. After the scandal of lecture and his student were reported in university newspaper, the university made a committee. When answering the question, David giving no clue to the judges. David was making confusing issues to them. The committee not wanted to force David to make apologize. They wanted to help David to keep doing his career by making a statement to make it clear. But he resisted by saying “I am being asked to issue an apology about which I may not be sincere?” (Coetzee, 1999: 58) David’s refusal to be “disgraced” can be read as a warlike strategy in the realm of sexual politics. For by renouncing the assault, David transfers the shame he feels upon Melanie in an attempt to strengthen his wavering masculinity and suppress her intimidating femininity. He plead guilty when he was in the committee. He remains silent and giving no story from his side. When David asked someone in the neutral position that is his former wife, Rosalind. She told him that he should have known that he is too old to be meddling with other people's children. He should have expected the worst from the scandal. She also blame the two for all that happened. `Don't blame her! Whose side are you on? Of course I blame her! I blame you and I blame her. The whole thing is disgraceful from beginning to end. Disgraceful and vulgar too. And I'm not sorry for saying so.' (Cortzee, 1999: 45) David feels disgrace on himself but he still cannot accept it. He said nothing to the committee and plead guilty. But from her former wife explanation he cannot resist it. Even though he must be so angry when he heard what she said. But he controlled his emotion and accept the disgrace given by the rape. For earlier, David is described as “mildly smitten with Melanie” and that “it was no great matter: barely a term passed when he did not fall for one or other of his charges” (Coetzee, 1999: 11-12,). Masquerading as the tragic subject of the ungovernable impulse of Eros, David publically justifies and renounces the stigmatization of Melanie’s rape.David’s lack of a sincere apology and his refusal to publically acknowledge the assault, along with his fanciful illustration of himself as a “servant of Eros” (Coetzee, 1999: 52) demonstrates the way in which disgrace (though masked as desire) is felt by men as a response to threatening femininity. Spurned and embarrassed by the loss of his womanizing charms, David’s shame is directed into lust, later to be passed off as “Eros” when he encounters Melanie Isaacs, whom he refers to as “Melanie: the dark one” (Coetzee, 1999: 8). As with Soraya, David’s seduction of Melanie is an attempt not only to reclaim sexual privilege, but to emphasize the traditional patriarchal procedures of the European culture, in which such privilege, like Lurie himself, is embedded. The worst thing from David’s disgrace is how he, an intellectual person which had title a professor, becomes a person who can do nothing except working in bad place. To be a dog-man, that he already underestimate it on Petrus. By the time, David realized that he can’t do nothing but accept what the destiny does. The situation that makes him to take any job turned David into a rational man. What David has and does in the university, which let him to become an intellectual people, disappear when he moved out. He then realized that what he writes about Byron and natural poets all this time is all about the death person. He never writes something in contemporary. CONCLUSION There will be two conclusions which are in line with the statement of problems. The first conclusion is about the depiction of rape in the novel Disgrace. The second conclusion is about how rape lead to shame through the rapist and the rape survivor. From the analysis that has been done about the depiction of rape. It can be concluded that that the author, J.M. Coetzee use the rape to describe the condition of race in post apartheid. All the rape in this novel is interracial rape. There are three kinds of rape experienced by three female characters. The first and the second rape was done by David, white male character that desiring ethnic women. He lived in promiscuity or womanizer that used to have sex with a lot of women. Then in the end he involved in scandal with his student, Melanie. Then the third rape was done to David’s daughter, Lucy. She was being raped by three African intruders. The first rape is happened between David and the prostitute, Soraya. On his age of 50 he has no plan to married again. Thus, it made David rely on prostitution in his sexual life. His ideal marriage is with a wife that is a prostitute, but for him only and only at certain times. He met Soraya only on Thursday. On the other day he is back to his normal life. With Soraya he already find the happiness he belief. It makes him thought; there is no need to search for another life destination such as home and real wife. Prostitution gives the solution that allows him to fantasize a woman to mirrors his wishes. This can be classified as rape concerning that every women in prostitutes would leave if they can and she has to do it because there are no other choices. But in the end Soraya decided to quit the job as prostitutes so he has no other place to suit his lust. Then, accidently David met Melanie on the way home. She is his student from romantic class. Melanie is a colored girl, this make David interest to her concerning that he is desiring ethnic women. He forced her to have sex. He did not force her physically but seduced her with suggestive words. The relationship between them then became a scandal in the campus and also became the talk of the city. He left the town and visits his daughter in other town to run away from the situation. During his visits to his daughter, three black men attack Lurie and Lucy at home. The men lock Lurie in a bathroom and rape Lucy in the bedroom. The second half of the novel deals with the aftermath of that moment. Lucy did not want to tell the police and keep silent about what happened to her. She also rejected her father offer to move to Holland. She claimed that it is a private matter and not to be shared. With nothing to left she got nothing to lose. Then she decided to take consequences of human body in pain. Accepting the subordinates , she is willing to sacrifice herself, brings peace between the different racial groups in South Africa. The second conclusion is about how rape lead to shame. In Disgrace the rape that experienced by the rapist and the rape survivor transform their life worst then before. The act of rape means to take away by force which the dignity is to be taken. Loosing dignity makes woman feel shameful on herself. While the rapist that considered as a thief will judge as disgraceful person after the rape. The male character, David Lurie, got disgrace after doing sexual harassment to his student, Melanie. As the rapist, David will be haunted by his sin and losing his reputation and his job. While Lucy, the rape survivor got shame after being raped The first shame is from the prostitute, Soraya. She felt the shame for being prostitute because every prostitutes is attached to shame. Then to keep her pride for her children, Soraya decided to quit the job. She did not want her children knows their real mother is. So she decided to resign from the escort and disappeared from that business. The second shame is from Melanie that involved in scandal with her lecture, David. She was shame for being reported even as victims. She often not attended the class even it was a midterm test. But she still survives to continue his study to university. This is maybe because David was kicked out from the university and not to be someone near her. The third shame is from Lucy, she raped by three African intruders. She is a lesbian that live alone in the small town. She thought that the rape that she got is the payment for living in South Africa. She felt that the rapist wants her to back home to Europe because the westerner’s does not belong to South Africa. Then she decided to stay and stay silent about the rape, and keeping her shame as a private matter. The last disgrace is from David, as rapist, David Lurie got public pressure from university committee and the students. At first he does not confess that he is guilty. He loses his job as a professor and turn to be an animal’s clinic assistance for killing unwanted dog. After her daughter raped by three African intruders he then contemplates and changes his attitude. He ask for apologize to Melanie’s family for his feeling guilty that he never confess before. The ending of the novel shows us that Lucy as the rape survivor could start her life again from the start. She continued to seeding a new plan even she is on pregnancy. He father, David, started to understand that he live in South Africa. Then, he stop complaining about the condition. Disgrace ends with Lurie staying on in Graham’s town, continuing to help out at the animal clinic. The open ending of the novel shows Lurie playing excerpts from his opera in the making on a makeshift toy banjo to the three legged dog, Driepoot, who is awaiting his turn for mercy killing. REFERENCE Abegunde, Babalola. 2013. Re-Examination of Rape and Its Groing Jurisprudance under International La. Journal of Politics and Law. Vol. 6, No. 4. Abbey, A., Parkhill, M., Clinton-Sherrod, A. & Zawacki T. 2007. A comparison of men who committed different types of sexual assault in a community sample. Journal of interpersonal violence. Baumeister, R., Catanese, K. & Wallace, H. 2002. Conquest by force: a nacissistic reactance theory of rape and sexual coercion. Review of general psychology Bushman, B., Bonacci, A., Dijk, M. & Baumeister, R. (2003). Narcissism, sexual refusal, and aggression: testing a narcissistic reactance model of sexual coercion. Journal of Personality and Social Psychology. Cahill, A. (2001). Rethinking rape. Ithaca: Cornell University Press Coetzee. J.M.. 1999. Disgrace. London: Vintage, 2000 Fuchs, Thomas. 2003. The Phenomenology of Shame, Guilt and the Body in Body Dysmorphic Disorder and Depression. Journal of Phenomenological Psychology. vol. 33, no. 2. Gottfredson, M. & Hirschi, T. 1990. A general theory of crime. Stanford: Stanford University Press Lowell, Gary. 2010. A Review of Rape Statistics Theories and Policy. Undergraduate Review. Massachusetts: Bridgewater State University. Nurka, Camille. 2012. Feminine Shame/Masculine Disgrace. Journal of Cultural Study. University of Melbourne Prentky, R. & Knight, R.1991. Identifying Critical Dimensions for Discriminating Among Rapists. Journal of Consulting and Clinical Psychology Siegert, R. & Ward, T. 2002. Rape and evolutionary psychology: a critique of Thornhill and Palmer’s theory. Journal of Aggression and violent behavior